Estudo do processo de sinterização a laser de materiais cerâmicos óxidos - Oliveira, Tiago Cordeiro de (2015)
Recently the laser sintering process has attracted the attention of researchers due to advantages such as: possibility of using very high heating and cooling rates, possibility of sintering materials with high melting point, among others. It has been observed that each material responds differently to the incident laser radiation, i.e., the same power density can generate different temperatures and temperature gradients that depend of the physics characteristics of the material. The correlation between these properties and the laser sintering process has been scarcely discussed in the literature, thus become it an important study subject for laser sintering process optimization. In this doctoral study, the main objective was the study of the laser sintering kinetics of common oxides, making a comparative study between experimental results and simulations of Fourier´s Law for heat conduction in solids. Ceramic bodies of TiO2, ZnO, CaTiO3 and Y2O3 pure and doped were produced starting from powders synthesized by the polymeric precursors method. For the production and characterization of the samples were used the Differential Thermal Analysis, Thermogravimetry, X-Ray Diffraction, Dilatometry, Scanning Electron Microscopy, radioluminescence, X-ray Fluorescence Spectroscopy and Impedance Spectroscopy. The four studied compositions obtained presented single crystalline phase. The numeric solution of the heat flow equation for Gaussian e Linear profiles allowed the analyses of specific situations of the temperature in function of the thermal conductivity, spot size, sample thickness and optical absorption coefficient. Significant correlations between the experimental observations and simulated data were obtained, mainly in the analyzes of the thermal properties. The results presented in the present work strengthen the understanding of the laser sintering technique for oxide systems and allow a considerable advance for the study of new systems.